A critical realist evaluation of an integrated care project for vulnerable families in Sydney, Australia - E. Tennant; E. Miller; K. Costantino; D. De Souza; H. Coupland; P. Fotheringham; J. Eastwood (BMC, 2020)
Abstract Background Healthy Homes and Neighbourhoods (HHAN) Integrated Care Initiative was established to improve the care of families with complex health and social needs who reside in Sydney Local Health District. HHAN seeks to provide long-term multi-disciplinary care coordination as well as enhance capacity building and promote integrated care. The critical realist study reported here is part of the longitudinal development and evaluation of complex integrated health and social care interventions in Sydney, Australia. Methods We describe the qualitative component of a critical realist pilot case study aimed at exploring, explaining and refining emerging HHAN programme theories in relation to care coordination. Qualitative interviews were undertaken with HHAN clients (n = 12), staff and other stakeholders (n = 21). Interviews and coding used a context (C), mechanism (M) and outcome (O) framework. Inductive, deductive, retroductive and abductive modes of reasoning were used with the CMO heuristic tool to inform the developing programme theory. Results The mechanisms underpinning effective engagement of clients by care coordinators included: building trust, leveraging other family, social and organisational relationships, meeting clients on their own terms, demonstrating staff effectiveness as quickly as possible, and client empowerment. Mechanisms for enhancing care integration included knowledge transfer activities and shared learning among collaborators, structural and cultural changes, enhancing mutual respect, co-location of multidisciplinary and/or interagency staff and cultivating faith in positive change among staff. Conclusions Use of a critical realism case study approach served to elucidate the varied influences of contexts and mechanisms on programme outcomes, to highlight what works for whom and in what context. Findings supported the initial programme theory that engagement and trust building with clients, alongside enhanced collaboration and integration of services, improved outcomes for vulnerable families with complex needs. Further research is needed to explore the cost-effectiveness of integrated care initiatives, in view of the long term nature of service provision and the risk of staff burnout.